Evaluation of the integrated disease surveillance and response system for infectious diseases control in northern Ghana - Adokiya, Martin Nyaaba; Awoonor-Williams, J. Koku; Barau, Inuwa Yau; Beiersmann, Claudia; Müller, Olaf (BMC public health, 2015)
Well-functioning surveillance systems are crucial for effective disease control programs. The Integrated Disease Surveillance and Response (IDSR) strategy was developed and adopted in 1998 for Africa as a comprehensive public health approach and subsequently, Ghana adopted the IDSR technical guidelines in 2002. Since 2012, the IDSR data is reported through the new District Health Information Management System II (DHIMS2) network. The objective was to evaluate the Integrated Disease Surveillance and Response (IDSR) system in northern Ghana.
Gesehen am 04.11.2020